Dividend Policy as a Moderator of Financial Ambidexterity on Firm Value - Utomo, Kukuh Hadi; Widhiastuti, Susanti; Ahmadi, Slamet (EAJ (Economic and Accounting Journal), 2025)
Tobin's Q, as a measure of firm value, holds significant importance as it encapsulates investor perceptions as well as prevailing conditions within the capital market. It is posited that the implementation of dividend policy may enhance the impact of Financial Ambidexterity on firm value. To substantiate this hypothesis, the present study was designed to analyze both the strengths and weaknesses of this influence. The analysis involved a sample comprising 49 data points collected from 13 companies operating within the banking sector of the financial services sub-sector, specifically covering the period from 2019 to 2023. The method applied is quantitative with purposive sampling technique. Statistical analysis was carried out at a significance level of 5% using the WarpPLS7.0 application. The research results obtained ROI and GPM partially affect the value of the company. ROE partially has no effect on firm value. DPR is unable to moderate the partial effect of ROI, GPM, and ROE on firm value. These results are a concern for companies to maintain the value of their ROI and GPM ratios because they are proven to have an influence.